2003
DOI: 10.1103/physrevlett.91.112001
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for Glueballs in Electron-Positron Annihilation

Abstract: We calculate the cross section for the exclusive production of J P C = 0 ++ glueballs G0 in association with the J/ψ in e + e − annihilation using the pQCD factorization formalism. The required long-distance matrix element for the glueball is bounded by CUSB data from a search for resonances in radiative Υ decay. The cross section for e + e − → J/ψ + G0 at √ s = 10.6 GeV is similar to exclusive charmonium-pair production e + e − → J/ψ + h for h = ηc and χc0, and is larger by a factor 2 than that for h = ηc(2S)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 21 publications
3
60
0
Order By: Relevance
“…There is no evidence for the sharp rise in cross-section for large | cos(θ prod )| expected for J/ψ J/ψ production via two virtual photons [3]. The prediction for a spin-0 glueball contribution (e + e − → J/ψ G 0 ) to the J/ψ η c peak, 4], is also disfavored. The process e + e − → γ * → J/ψ χ c0 can proceed via both S-and D-wave amplitudes, and predictions for the resulting angular distributions are therefore model dependent.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…There is no evidence for the sharp rise in cross-section for large | cos(θ prod )| expected for J/ψ J/ψ production via two virtual photons [3]. The prediction for a spin-0 glueball contribution (e + e − → J/ψ G 0 ) to the J/ψ η c peak, 4], is also disfavored. The process e + e − → γ * → J/ψ χ c0 can proceed via both S-and D-wave amplitudes, and predictions for the resulting angular distributions are therefore model dependent.…”
mentioning
confidence: 93%
“…[3] have proposed that processes proceeding via two virtual photons may be important. Other authors [4] suggest that since the dominant mechanism for charmonium production in e + e − annihilation is expected to be the color-singlet process e + e − → ccgg, the final states observed by Belle contain a charmonium state and a M ∼ 3 GeV/c 2 glueball. Such glueball states are predicted by lattice QCD and can have masses around 3 GeV/c 2 .…”
mentioning
confidence: 99%
“…In particular, Bodwin, Braaten, and Lee proposed [9,10] that processes proceeding via two virtual photons may be important, and Belle data for J/ψ + η c might essentially include the J/ψ + J/ψ events which were produced via two photons. Brodsky, Goldhaber, and Lee suggested that since the dominant mechanism for charmonium production in e + e − annihilation is expected to be the color-singlet process e + e − → ccgg, the final states observed by Belle might contain J/ψ and a M ∼ 3GeV spin-J glueball G J (J = 0, 2) [11]. Motivated by these proposals, Belle presented an updated analysis [12], and ruled out the J/ψ +J/ψ and spin-0 glueball scenarios.…”
mentioning
confidence: 99%
“…Thus, the anomalous production remains one of the challenging problems in QCD, and arouses speculations. For example, a heavy glueball of a mass very near m ηc with a rather large matrix amplitude has been proposed [10] to account for the excess.…”
Section: +0007mentioning
confidence: 99%